Hier irrte Einstein - Sallhofer, Hans H (World Scientific, 2001)
Includes bibliographical references (p. 189-194) and index; This book contains a dialogue between a physicist and a philosopher on that issue. The dialogue is strongly contextualized with respect to the main players in physics during the first sixty years of the 20th century, and to the prevailing political conditions in Western Europe and the USA. It was galvanized by the debate and the subsequent abandonment of the Superconducting Super Collider, and also affords a lively understanding of Greek epistemology. Questioned by the philosopher, the physicist provides an account of the directions taken by physicists and the roads not traveled, as well as his own understanding of the nature of matter.